2017
DOI: 10.1007/s00246-017-1607-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Association in the Cardiac Hypertrophy Secondary to Complex Congenital Heart Disease in Children

Abstract: Complex congenital heart disease (CHD) affects cardiac blood flow, generating a pressure overload in the compromised ventricles and provoking hypertrophy that over time will induce myocardial dysfunction and cause a potential risk of imminent death. Therefore, the early diagnosis of complex CHD is paramount during the first year of life, with surgical treatment of patients favoring survival. In the present study, we analyzed cardiac tissue and plasma of children with cardiac hypertrophy (CH) secondary to CHD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Heart dilation has been seen in humans subsequent to a previous diagnosis of a hypertrophic heart, suggesting the heart is failing (Hamada et al ). Conversely, the developing or postnatal heart with a complex congenital defect (having two or more heart defects) is prone to abnormal haemodynamics, with a dilated heart seen as a secondary effect in some cases (Sanchez‐Gomez et al ; Courchaine et al ). In addition, a recent study has indicated that as heart development progresses (HH22 to HH36), the proximal part of the OFT (conus) becomes part of the right myocardial wall (Lazzarini et al ); this process could rescue the right ventricular wall from a dilating phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart dilation has been seen in humans subsequent to a previous diagnosis of a hypertrophic heart, suggesting the heart is failing (Hamada et al ). Conversely, the developing or postnatal heart with a complex congenital defect (having two or more heart defects) is prone to abnormal haemodynamics, with a dilated heart seen as a secondary effect in some cases (Sanchez‐Gomez et al ; Courchaine et al ). In addition, a recent study has indicated that as heart development progresses (HH22 to HH36), the proximal part of the OFT (conus) becomes part of the right myocardial wall (Lazzarini et al ); this process could rescue the right ventricular wall from a dilating phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a marked increase of ventricular pressure seen in OFT‐banded embryos (Shi et al ), heart rate and cardiac output/ejection fraction were not affected (Clark et al ), suggesting preservation of ventricular function. Therefore, OFT‐banding is a model for a heart with a complex congenital heart defect phenotype that is prone to abnormal haemodynamics and pressure overload, and hence heart enlargement (Sanchez‐Gomez et al ). Expression analysis in such hearts could pinpoint molecular pathways that may have protective or conversely debilitating long‐term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac hypertrophy caused by CHD was found to be related to higher expression of miR-1, miR-18b, miR-21, miR-23b, miR-133a, miR-195, and miR-208b in heart tissue. According to Sánchez-Gómez et al (2017), miR-21, -23a and -24 can be considered specific biomarkers for the diagnosis of cardiac hypertrophy in infants with CHD [127]. Expression levels of miR-24 were found to strongly correlate with GATA-4 and MEF2c transcription factors that are linked to the heart's development, regulating the differentiation of precardiac mesoderm and morphogenesis.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Expression levels of miR-24 were found to strongly correlate with GATA-4 and MEF2c transcription factors that are linked to the heart's development, regulating the differentiation of precardiac mesoderm and morphogenesis. miR-1 was strongly associated with cell damage and miR-133a moderated the expression of beta-myosin heavy chains (β-MHC) in children with CH [127]. To elaborate further on research carried out by to Sánchez-Gómez et al, Zloto et al (2020) found miR-208a to be of relevance as a promising biomarker of postoperative complications in pediatric patients with CHD who underwent surgery [128].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Several studies have documented the effects of high concentrations of PFCs on humans [2,16,36], yet a low concentration of PFCs exposure should still be a concern. Recently, low-level PFCs in the environment have been reported to cause gene alteration and may lead to the risk of developing CVDs [37,38]. Cumulated data suggest that the risks of CVDs are raised by environmental exposure [39,40].…”
Section: Introductionmentioning
confidence: 99%